The influence of CD40 ligation and interferon-γ on functional properties of human monocyte-derived dendritic cells activated with polyinosinic-polycytidylic acid - Dragičević Ana; Džopalić Tanja; Vasilijić Saša; Vučević Dragana; Božić Biljana; Majstorović Ivana; Balint Bela; Čolić Miodrag (Vojnosanitetski Pregled)
Background/Aim. Ligation of a Toll-like receptor (TLR) by specific TLR agonists is a powerful tool for maturation induction of monocyte-derived dendritic cells (MoDCs). Studies so far have shown that the treatment of dendritic cells (DCs) with a TLR3 ligand, polyinosinic-polycytidylic acid [Poly(I:C)], may be an appropriate activation agent for obtaining mature MoDCs, competent to prime effective immune responses. However, little is known about how subsequent interaction of MoDCs with T cell-derived stimuli, such as CD40 or interferon-γ (IFN-γ), modulates MoDC functions. Therefore, this problem was the main objective of this study. Methods. Immature MoDCs were prepared by cultivation of monocytes from peripheral blood mononuclear cells with granulocyte macrophage-colony stimulating factor (GM-CSF) and interleukin (IL)-4 for 5 days. After that, maturation was induced by the treatment of these cells with Poly(I:C) for 2 days. At day 6, immature MoDCs and Poly(I:C)-activated MoDCs were incubated either with CD40 ligand (L)-transfected J558 cells or IFN-γ for additional 24 hours. Cytokine production was measured by ELISA and FlowCytomix Human T helper Th1/Th2 11plex. Allostimulatory capability of MoDCs was tested using an allogeneic mixed leukocyte reaction (MLR) assay. Results. Immature MoDCs showed a moderate potential for stimulation of proliferation of CD4+ T cells, which was enhanced by the treatment with Poly(I:C). Ligation of CD40 or treatment with IFN-γ of immature or Poly(I:C)-treated MoDCs significantly up-regulated their allostimulatory activity. MoDCs matured in the presence of Poly(I:C) up-regulated the production of IL- 12 and IL-10, which was followed by increased levels of IFN- γ and decreased levels of IL-5 in co-cultures with allogeneic CD4+ T cells. Ligation of CD40 on immature MoDCs upregulated the production of IL-12 and IL-23 which was accompanied by increased secretion of IFN-γ in co-culture. Stimulation of CD40 on Poly(I:C)-treated MoDCs significantly enhanced the production of IL-12, IL-23 and IL-10. However, such treated MoDCs decreased the production of IFN-γ and IL-10 and up-regulated the secretion of IL-17. Immature MoDCs treated with IFN-γ up-regulated IL-12, but lowered the production of IL-5 and IL-17 by CD4+ T cells. Treatment of Poly(I:C)-activated MoDCs with IFN-γ down-regulated the production of IL-12 and up-regulated IL- 10 by these cells and increased/decreased the levels of IL-10/ IFN-γ, respectively, in co-culture with CD4+ T cells. Conclusion. Treatment with Poly(I:C) or ligation of CD40 on immature MoDCs induces maturation of these cells into a phenotype that supports Th1 response. Activation of CD40 on Poly(I:C)-treated MoDCs shifts the immune response towards Th17. Treatment of immature MoDCs with IFN-γ down-regulated Th2 and Th17 responses. However, addition of IFN-γ to Poly(I:C)-activated MoDCs down-regulated Th1 response and promote T regulatory mechanisms. Each of these results may have functional and therapeutic implications.